O Diretor de Escola Pública que profissional é este? - Igreja, Maria Aparecida Fava (2008)
This study has as its purpose to research over the public school principal, reflecting his daily routine, his perspectives and achievements, in order to better meet the so many different tasks to him attributed. For so, a theoretical and bibliographic investigation about the public school management, its social objective, autonomy and the search for the quality from the offered education was held. The open examination process and the recycling of professional competences provided by SEE to public school management board through Progestão were also analyzed. Four school principals from Sao Paulo and Grande ABC region were interviewed concerning their daily practices, tensions, difficulties and performance. The school management in a multirreferential perspective was indicated as a possible solution for this research question.(AU)